Using Fables to Assist Students in Enhancing Their Reading Comprehension - Saputra, Frian; Kurniawati, Ari; Dewi, Nurmala; Nurhasanah, Indri; Hartati, Berli (Journal of English Education, 2023)
The main problem in this study was "Is it effective to teach reading comprehension by using fables to the eleventh-grade students at SMK Rawas Hulu?". The objective of this study is to find out whether or not teaching narrative text by using fables to eleventh-grade students at SMK Rawas Hulu is effective. The method used in this study was the quasi-experimental method. The population of this research was the eleventh-grade student at SMK Rawas Hulu in the academic year of 2022/2023. The population was 240 students, and 240 students were taken as samples, which were chosen through purposive sampling in the form of convenience sampling. The written test was used to collect the data and analysed through paired samples t-test. The result of this study proved that are the fables effective for teaching reading comprehension by using fables to the eleventh-grade students at SMK Rawas Hulu, it is proved by the degree of freedom (df) 33, sig with 2-tailed 0,000. T- obtained shows that the alternative hypothesis with 95% (0,05) of the significant level was accepted because the result of paired samples t-test was 3.088 which exceeded the t-table value was 2,042 as its critical value under 0,05 significant levels. Besides, the alpha value It (0,000) was less than 0,05. it indicated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that Teaching Reading Comprehension by Using Fables to The Eleventh Grade Students at SMK Rawas Hulu was effective.